Corpus Study of the Adverb of Degree ‘Feichang’ in Chinese and English Parallel Corpus - Clara Herlina Karjo; Mei Rianto Chandra (Journal of English as A Foreign Language Teaching and Research, 2024)
The use of a parallel corpus for Chinese and English adverbs is still rarely explored, especially when comparing the Chinese adverb feichang with its English equivalents. ‘Feichang’ literally means "very", but English has various other words to convey the same words. The aim of this study is to compare the grammatical structure and semantic meaning of the Chinese adverb ‘feichang’ with its English equivalents using Chinese-English parallel corpus. To obtain the data, we used 50 sentences that contain the word ‘feichang’ in Chinese and English from the PKU parallel corpus. All sentences are related to the computer field. These sentences were then analyzed using AntConc, a concordance tool, to examine the grammatical structure and semantic aspects of the phrases. The findings showed that in Chinese, the adverb ‘feichang’ occurs in adjective and verb phrases. Meanwhile, in the English corpus, these phrases are rendered differently in five types of phrases: adjective, noun, verb, prepositional, and adverbial. Moreover, the word ‘feichang’ itself is rendered in a different lexicon, even though the meaning is the same. The results implied that one language can offer more varieties in expressing similar ideas, and parallel corpus can be a good source for analyzing these differences.